LIBRARY APPLICATIONS MASJID AL-MUJAHIDIN USING PHP AND MYSQL - Dili Yanto; Yulina, SKom, MMSI Yulina, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Scientific writing is about the making of the Public Library Application usingsoftware (software), which is like the language application programan PHP andMySQL for its database. These applications in addition to containing informationabout the Book Library also consists of transactions, library work processes, such asinput, output and library book lending library of books.In completing this writing, the writer did approach by reading the books, articles andbrowsing on the Internet to get information as much as possible so it can be used tosolve the problem in this writing.